The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s12094-012-0857-4
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Hif1-α interacting proteins in renal cell carcinoma

Abstract: Introduction. Kidney tumours are frequently characterised by hypoxic conditions due to a local imbalance between oxygen (O 2 ) supply and consumption. Hif1-α regulates angiogenesis, tumour growth, tumour progression, metastatic spread, and glucose metabolism by acting as a transcription factor for relevant genes. Here, we describe an immunohistochemical study of Hif1-α, a comprehensive computational study of Hif1-α interacting proteins (HIPs), an analysis correlating expression levels of Hif1-α with upstream a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The protein products of these genes participate in both protecting the cell against hypoxia and activating angiogenesis. Among the genes in question there are carbonic anhydrase 9, vascular endothelial growth factors and their receptors, glucose transporter 1 and others [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The protein products of these genes participate in both protecting the cell against hypoxia and activating angiogenesis. Among the genes in question there are carbonic anhydrase 9, vascular endothelial growth factors and their receptors, glucose transporter 1 and others [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Schultz et al [61] showed that HIF1α levels were significantly higher in primary and metastatic ccRCCs compared with benign tissues (P<0.0001), and that tumor size and HIF1α expression were independent predictors of both reduced disease free survival and tumor progression in primary ccRCC. In another recent report, the highest level of HIF1α expression in ccRCCs was associated with the worst prognoses [60]. Studies have also examined both HIF1α and HIF2α in the same tissue samples.…”
Section: Reviewmentioning
confidence: 99%
“…Of note, HIF1α expression correlates significantly with the “clear” histological subtype of renal cell carcinoma (p<0.01) [60], possibly because HIF1α (and not HIF2α) increases the expression of lipin1, a phosphatidate phosphatase that catalyzes the last step in triglyceride biosynthesis [64]. Triglycerides form lipid droplets, the major neutral lipid stores in cells, and these lipid droplets cause the “clear” phenotype in human ccRCC.…”
Section: Reviewmentioning
confidence: 99%
“…The functional form of the pVHL in association with elongin C, elongin B, cullin2 (Cul2), neural precursor cell expressed developmentally down-regulated 8 (Nedd8) and ring-box 1 (RBX1) forms a multi-protein complex called E3 ubiquitin ligase (or VEC) able in turn to bind the hydroxylated form of the subunit α of the transcription hypoxia-inducible factor (HIF) [4,5,6,7]. In normoxic conditions the formation of this complex leads to the degradation of HIF, while in case of hypoxia the stabilized form (non-hydroxylated) HIF is able to induce the transcription of genes that leads to the secretion of pro-angiogenic factors (such as vascular endothelial growth factor (VEGF) and platelet derived growth factor-β (PDGF-β)), Glucose transporter 1 (GLUT-1) and erythropoietin [4,5,6,7,8] (Figure 1). Over the last few years the ever-deeper knowledge on the molecular biology of metastatic RCC has led to the development of numerous molecular targeting agents (such as sunitinib, sorafenib, pazopanib, axitinib, tivozanib, and dovitinib) [9].…”
Section: Introductionmentioning
confidence: 99%